2020
DOI: 10.1101/2020.03.16.993568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-tolerant vascular endothelial growth factor-A (VEGF-A) and the genetic variations ofVEGFAin Sherpa highlanders

Abstract: 24Sherpa highlanders demonstrate extraordinary tolerance to hypoxia at high altitudes, 25 partly by one of the adaptation mechanisms promoting increases of microcirculatory 26 blood flow and capillary density at high altitude for restoring oxygen supply to tissues. 27 Hypoxia stimulates vascular endothelial growth factor (VEGF), which is an important 28 signaling protein involved in hypoxia-stimulated vasculogenesis and angiogenesis. Our 29 present study included 51 Sherpas dwelling in Namche Bazaar vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, human studies reported conflicting data regarding circulating VEGF-A levels in healthy sea level residents during short-term exposure to high altitudes [61,62]. Chronic exposure to hypoxia seems not to be associated with increased systemic VEGF levels in well-adapted Sherpa highlanders {Droma, 2020 #12125} [63]. Interestingly, patients with chronic mountain sickness exhibited higher VEGF expression compared to healthy Andean highlanders despite comparable peripheral oxygen saturation levels [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, human studies reported conflicting data regarding circulating VEGF-A levels in healthy sea level residents during short-term exposure to high altitudes [61,62]. Chronic exposure to hypoxia seems not to be associated with increased systemic VEGF levels in well-adapted Sherpa highlanders {Droma, 2020 #12125} [63]. Interestingly, patients with chronic mountain sickness exhibited higher VEGF expression compared to healthy Andean highlanders despite comparable peripheral oxygen saturation levels [64].…”
Section: Discussionmentioning
confidence: 99%